Jornalismo cultural: a produção de Patrícia Galvão no jornal A Tribuna - Costa, Márcia Rodrigues da (2008)
This study salvages Patrícia Galvão s participation in cultural journalism in the city of Santos, between 1954 and 1961, from a sociologic-historical perspective. From the study of her intellectual trajectory, it was possible to identify, through a qualitative analysis of the column Literature, produced by the journalist between 1957 and 1961 for the newspaper A Tribuna, the defining characteristics of her production in four decades of dedication to the press: the constant search for reporting the vanguard , the didactic preoccupation, the intellectual autonomy, the defense of literature as a form of social emancipation and the dialogue with local, Brazilian and foreign intellectuals and writers. This study has situated Patricia Galvão in a generation which contributed to modernize the discussion of ideas and the very language of the magazines and periodicals in which they participated. The production of these intellectuals stressed the role of newspapers as an instrument of analysis and criticism in face of the discussions on culture and society, which allows the understanding of the press as a territory of conflicts which shelters different symbolic productions.